Climate change, pollution, and mental health: concerns on rising temperatures and polycyclic aromatic hydrocarbon risks - Chisom Ejileugha; Ekpo Otu (Discover Environment)
Abstract The rising global temperatures due to climate change have a profound impact on global health. Heat is associated with many physical and mental health conditions. The impact of heat on health could be exacerbated in polluted areas due to the combined impact of pollutants and heat stress. Polycyclic aromatic hydrocarbons (PAHs) are among environmental pollutants of public health significance. Exposure to PAHs has adverse effects on physical and mental health and these effects could be worse in oil-impacted communities due to increased PAH exposure and environmental degradation. Heat increases the volatilisation of PAHs, mobility and availability of PAHs, formation of toxic PAH derivatives, and possible wildfire incidents which introduce more PAHs into the environment. This increases human exposure to PAHs through various pathways, in addition to heat stress, thereby worsening mental health challenges. The anticipated decrease in PAH levels due to reduced emissions is offset by the impact of rising temperatures, which promote the mobilisation and volatilisation of existing PAHs. Therefore, this review highlighted the combined risks of heat and PAHs amid rising global temperatures, especially in oil-impacted communities. The various mechanisms through which heat could increase PAH risks were also highlighted. Possible pollution prevention, exposure mitigation, and environmental and public health intervention approaches were suggested. Rapid oil spill response, environmental remediation, ecosystem restoration, biomonitoring, environmental, and agro products monitoring could help mitigate exposure. Additionally, the introduction of green education, mental health impact assessment for every project, and investment in sustainable green technologies by the oil companies. Overall, this review creates awareness of the neglected impact of heat on PAH risks and draws the attention of researchers, funders, policymakers, and society to approaches to mitigate PAH risks as we navigate the challenges of climate change. Graphical Abstract